Life cycle assessment of tunnel structures: Assessment of the New Austrian Tunnelling Method using a case study. Issue 1 (1st September 2022) - Hopf, Bernhard W.; Hoxha, Endrit; Scherz, Marco; Heichinger, Harald; Kreiner, Helmuth; Passer, Alexander
Abstract: One important measure to combat progressing climate change is compliance with and under no circumstances to exceed the decreasing greenhouse gas budget. Every economic sector must strive to make its ecological contribution to achieve this objective. The construction sector is largely responsible for these negative environmental burdens. Although tunnels are considered to have extensive energy and material consumptions the literature has failed to present their environmental impacts. Aimed at this knowledge gap, the objective of this study is to present the life cycle assessment (LCA) of a tunnel construction project situated in Bulgaria. The study analyzes the impacts of the New Austrian Tunnelling Method (NATM) using the case study "Modernization of Railway Section Elin Pelin-Kostenets – Lot 3". Moreover, by applying dominance and sensitivity analyses, the environmental drivers and optimization potential for reducing greenhouse gas emissions are identified. The results show that steel, shotcrete, and concrete, contribute the most to the global warming potential indicator and are responsible for 85% of this. Furthermore, the life cycle stages for the production of materials and components have a share close to 85 % of the total global warming potential. These findings may help future tunnelling construction projects to improve the environmental performance and thus to combat the alarming development of climate change.